Violence Against Women and Children Through Social Media - Purba, Niko; Runturambi, Arthur Josias Simon; Nita, Surya (SAINTIS Publishing, 2025)
Violence against women and children is increasingly occurring through social media, as the use of digitized technology increases. This research aims to investigate some of the elements that contribute to violence against women and children on social media, as well as the impacts faced by victims. The research used an extensive literature evaluation, analyzing various related texts, journals and research papers. The results show that the main causes of violence against women and children on social media include patriarchal culture, lack of digital literacy, user anonymity, weak regulation and law enforcement, and normalization of violence in the digital space. The impacts include psychological, social, and economic disruption for victims. Based on these findings, this research provides recommendations for improving digital literacy for the community, strengthening legal regulations related to gender-based forms of violence in the realm of social media, and working together with the government, social media, and community organizations to develop a safer and more inclusive digital landscape.